Seasonal variation of leaf yield in mulberry raised under bio and organic treatments in drought prone lateritic zone of West Midnapur,West Bengal - Chakraborty, Barna; Chakraborty, Susanta Kumar (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2015)
Seasonal sensitivity of mulberry in drought prone lateritic zone of Midnapore(West)wasinvestigated under different organic and bio-fertilizer treatments during 2004-2006.The fieldexperimental study was conducted for four successive seasons (Rainy, Autumn, Spring,Summer), from August to May in lateritic soil condition (having around pH of 5.6) with limitedirrigation support in some areas of Midnapore(West) Districts, West Bengal, India. Theplantation was raised in lateritic soil of Vidyasagar University campas (22o 25/ N latitude and87o 17/ longitude) of Paschim Midinapore, West Bengal,India.. The study aimed to focus theeffect of season on yield of mulberry during four consecutive seasons. Results with respect ofyield of leaves in different crop seasons indicated that the August crop season /(rainy) exertedmore influence than any other crop season and recorded the highest yield (3642.02kg./ha./season), followed by February/ spring (3589.01 kg./ha./ season), November/ Autumn(3587.89 kg./ha./season) and May/ summer (3586.18 kg./ha./season) based on interactionbetween seasons and treatments.Although application of poultry manure along with biofertilizers and reduced doses of inorganic fertilizers(T3) was found to be highest yielder (3916.03kg./ha./season) influenced by August crop season; but equal attempts provided by sametreatment also observed in other crop seasons highlighted the dominancy of treatments overseasons.